Advances in screening and diagnostic lab-on-chip tools for gynaecological cancers – a review - Sadeka Nujhat; Hannah S. Leese; Mirella Di Lorenzo; Rebecca Bowen; Sandhya Moise (Artificial Cells, Nanomedicine, and Biotechnology, 2023)
AbstractGynaecological cancers are a major global health concern due to the lack of effective screening programmes for ovarian and endometrial cancer, for example, and variable access to vaccination and screening tests for cervical cancer in many countries. Recent research on portable and cost-effective lab-on-a-chip (LoC) technologies show promise for mass screening and diagnostic procedures for gynaecological cancers. However, most LoCs for gynaecological cancer are still in development, with a need to establish and clinically validate factors such as the type of biomarker, sample and method of detection, before patient use. Multiplex approaches, detecting a panel of gynaecological biomarkers in a single LoC, offer potential for more reliable diagnosis. This review highlights the current research on LoCs for gynaecological cancer screening and diagnosis, emphasizing the need for further research and validation prior to their widespread adoption in clinical practice.